Fabrication of NPB/Alq3 small‐molecule multilayer structures with suppressed interface mixing by multi‐jet mode electrospray deposition. Issue 2 (14th December 2016) - Ueda, Hiroyuki; Takatsuka, Yusuke; Niinuma, Yoshiki; Terada, Ryo; Kikuchi, Akihiko
Abstract : In this study, we investigated the multi‐jet mode modified electrospray deposition (ESD) production of NPB/Alq3 small‐molecule multilayer structures with suppressed interface mixing, using common solvents. Observations of the initial deposition stage and analysis of the photoluminescence spectra of the multilayer structure were conducted. It was demonstrated that, by optimizing the deposition conditions, surface erosion of the NPB layer and the initiation of interface mixing between the NPB and Alq3 layers could be suppressed. A 55‐nm NPB/60‐nm Alq3 multilayer structure with suppressed intermixing and smooth surface morphology (RMS roughness of 3.9 nm) was obtained at the lowest levels of under‐layer erosion. Schematic of a modified electrospray (nanomist deposition: NMD) system and an NPB/Alq3 multilayer structure deposited by NMD.